'Teacher, what is history for?' A reflection on the practical function of history - Mendanha Cruz, Matheus (Universidad Nacional del Litoral, 2020)
The following text defends, through theoretical reflection, the relevance of science as a guide for actions in the present and a method for the construction of knowledge. What can the historian do so that the past can be valued as an orientation for practical life? The article starts from the assumption that the Didactics of History is an area of ​​historical science that proposes the organization of this reflection. The title of the text is the reproduction of a question experienced in the classroom by almost all teachers in this discipline.